MAFB modulates the maturation of lymphatic vascular networks in mice. Issue 10 (7th July 2020) - Rondon‐Galeano, Maria; Skoczylas, Renae; Bower, Neil I.; Simons, Cas; Gordon, Emma; Francois, Mathias; Koltowska, Katarzyna; Hogan, Benjamin M.
Abstract: Background: Lymphatic vessels play key roles in tissue fluid homeostasis, immune cell trafficking and in diverse disease settings. Lymphangiogenesis requires lymphatic endothelial cell (LEC) differentiation, proliferation, migration, and co‐ordinated network formation, yet the transcriptional regulators underpinning these processes remain to be fully understood. The transcription factor MAFB was recently identified as essential for lymphangiogenesis in zebrafish and in cultured human LECs. MAFB is activated in response to VEGFC‐VEGFR3 signaling and acts as a downstream effector. However, it remains unclear if the role of MAFB in lymphatic development is conserved in the mammalian embryo. Results: We generated a Mafb loss‐of‐function mouse using CRISPR/Cas9 gene editing. Mafb mutant mice presented with perinatal lethality associated with cyanosis. We identify a role for MAFB in modifying lymphatic network morphogenesis in the developing dermis, as well as developing and postnatal diaphragm. Furthermore, mutant vessels displayed excessive smooth muscle cell coverage, suggestive of a defect in the maturation of lymphatic networks. Conclusions: This work confirms a conserved role for MAFB in murine lymphatics that is subtle and modulatory and may suggest redundancy in MAF family transcription factors during lymphangiogenesis. Key Findings: We generate a novel MafB loss-of-function mouse model using CRISPR genome editing. MafB plays a conserved role in developmental lymphangiogenesis. MafB modulates lymphatic vascular network morphogenesis in the developing dermis and postnatal diaphragm. This work identified MafB as an important developmental transcription factor in vascular network formation.